PENGEMBANGAN KOMBINASI MODEL PEMBELAJARAN BERBASIS MASALAH DAN INKUIRI TERBIMBING PADA PEMBELAJARAN KIMIA LARUTAN DI SMA KELAS XI UNTUK MENINGKATKAN HASIL BELAJAR KIMIA DAN KARAKTER SISWA - Grace Eunike Sinaga; Iis Siti Jahro; Mahmud Mahmud (Pascasarjana Universitas Negeri Medan, 2014)
Abstract : The Combination Development Model of Problem Based Learning and Guided Inquiry Lesson In Chemistry Solution In high school Class XI To Improve The Results of Chemistry Learning and Value of Character Students. This study aims to analyzed the difference of chemical enhancement of learning outcomes and character KKPGR and the relationship between character and chemical students outcomes of students who were taught significantly between Direct Instruction model, Problem Based Learning and Guided Inquiry, and Problem Based Learning and Guided Inquiry with computers, This studied was experimental. Sampling technique used purposive sampling , that was SMAN 2, SMAN 7 and SMAN 17 Medan respectively 3 classes. Based on the results of data processing, it was concluded Significantly there were differences in learning outcomes, character values and there is a relationship with the learning outcomes of the character values between students who were taught chemistry by learning model of Direct Instruction compared with the model of Problem Based Learning as compared with the integrated Guided Inquiry model of Problem Based Learning is integrated guided inquiry using computer.Keywords: Problem Based Learning, Guided Inquiry and Direct Instrusction